Bumbometer digital crowd game: collaboration through competition in entertainment events - Martins, Gustavo (2021)
The use of mobile devices, especially smartphones, is widespread across all social strata and age groups, helping to ensure faster access from anywhere, data collection, and more regular and frequent control to aid urban, environmental, and social management. In this scenario, the entertainment industry has benefited from this powerful individual technological resource in cultural and sporting events. In this way, this work presents a proposal for interaction and engagement in entertainment events in a more prosperous and more technological way, through the development of a collaborative and competitive mobile-web crowd game, intended for enhancing interaction between the crowd and as a unified group, whether physically co-located or online. The application, called Bumbometer, uses motion sensors during an interactive dynamic with the crowd applying concepts from Mobile Crowd Sensing and User eXperience. We conducted two experimental studies to evaluate the proposed technology, the first in a real scenario of a folk cultural festival and the second in a controlled environment, simulating an event considering a scenario in which users were geographically distant. The results indicate that people feel immersed and engaged during the interaction through the proposed game, which reinforces the statement that the game meets an increasingly growing need to use technologies to ensure more significant interaction and audience immersion at crowd entertainment events, a creative and far-reaching form.